PENGARUH KESEHATAN MENTAL TERHADAP KINERJA KARYAWAN SWASTA DI WILAYAH KOTA SURABAYA - Lelli Kisdayanti; Nur Farida (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
This study aims to determine the effect of mental health on employee performance. This research method is quantitative using simple linear regression data analysis techniques with the help of SPSS. The sampling technique in this study used purposive sampling with a sample size of 100 respondents. quantitative research on causal relationships looking for the influence of the independent variable on the dependent variable. The independent variable in this study is mental health, while the dependent variable is employee performance. The regression equation model in the form of a simple linear regression equation is as follows: Y = 6.453 + 0.316X: which means that if an employee's mental health increases by one unit, it will result in an increase in employee performance of 0.316. The results showed that mental health had an effect on the performance of private employees in Surabaya.